The Shotokan karate bible : beginner to black belt - Martin, Ashley, 1972- (Firefly Books, 2007)
The Shotokan Karate Bible is a comprehensive illustrated guide suitable for all students of Shotokan karate, from beginners to those earning a black belt. The author outlines and explains the lessons for all ten gradings. The book is organized by belt, and a syllabus lists the requirements for achieving each new level. The book includes all essential details that the karate student should know: The history of Shotokan karate, basic karate terms, the uniform, dojo etiquette and bowing, sparring safety tip, tips on taking grading exams, and training and development.